Enhanced-Bivium Algorithm for RFID System. (25th October 2015) - Zhang, Shiyong; Chen, Gongliang; Zhou, Yongkai; Li, Jianhua
Abstract : RFID (radio frequency identification) is an emerging technology for automatic identification of physical objects using radio frequency. The security and privacy of the system is increasingly concerned and some light-weight encryption schemes such as Trivium and Bivium have been proposed. In this paper, the internal structure of Bivium is exploited and generalized to an algorithm called Bivium-Model. It is shown that the original Bivium has its inherent imperfections due to the improper parameter selection. A set of better parameters are given out to fix the security vulnerability of original Bivium. Emulation results also show that the Enhanced-Bivium algorithm achieves lower power consumption and lower die size.